Hey there! :)
Answer:
h(x) = 3x² - 7x - 6
Step-by-step explanation:
Calculate h(x) by adding the two polynomials:
h(x) = f(x) + g(x):
h(x) = x² - 3x + 5 + 2x² - 4x - 11
Combine like terms:
h(x) = 3x² - 7x - 6
Answer:
0.01
0.000001
10,000
Step-by-step explanation:
i got it on edge
No, but “of” does. “Much”’s meaning can change depending on the context
Answer:
The functions satisfy the differential equation and linearly independent since W(x)≠0
Therefore the general solution is
![y= c_1x^4+c_2x^6](https://tex.z-dn.net/?f=y%3D%20c_1x%5E4%2Bc_2x%5E6)
Step-by-step explanation:
Given equation is
![x^2y'' - 9xy+24y=0](https://tex.z-dn.net/?f=x%5E2y%27%27%20-%209xy%2B24y%3D0)
This Euler Cauchy type differential equation.
So, we can let
![y=x^m](https://tex.z-dn.net/?f=y%3Dx%5Em)
Differentiate with respect to x
![y'= mx^{m-1}](https://tex.z-dn.net/?f=y%27%3D%20mx%5E%7Bm-1%7D)
Again differentiate with respect to x
![y''= m(m-1)x^{m-2}](https://tex.z-dn.net/?f=y%27%27%3D%20m%28m-1%29x%5E%7Bm-2%7D)
Putting the value of y, y' and y'' in the differential equation
![x^2m(m-1) x^{m-2} - 9 x m x^{m-1}+24x^m=0](https://tex.z-dn.net/?f=x%5E2m%28m-1%29%20x%5E%7Bm-2%7D%20-%209%20x%20m%20x%5E%7Bm-1%7D%2B24x%5Em%3D0)
![\Rightarrow m(m-1)x^m-9mx^m+24x^m=0](https://tex.z-dn.net/?f=%5CRightarrow%20m%28m-1%29x%5Em-9mx%5Em%2B24x%5Em%3D0)
![\Rightarrow m^2-m-9m+24=0](https://tex.z-dn.net/?f=%5CRightarrow%20m%5E2-m-9m%2B24%3D0)
⇒m²-10m +24=0
⇒m²-6m -4m+24=0
⇒m(m-6)-4(m-6)=0
⇒(m-6)(m-4)=0
⇒m = 6,4
Therefore the auxiliary equation has two distinct and unequal root.
The general solution of this equation is
![y_1(x)=x^4](https://tex.z-dn.net/?f=y_1%28x%29%3Dx%5E4)
and
![y_2(x)=x^6](https://tex.z-dn.net/?f=y_2%28x%29%3Dx%5E6)
First we compute the Wronskian
![W(x)= \left|\begin{array}{cc}y_1(x)&y_2(x)\\y'_1(x)&y'_2(x)\end{array}\right|](https://tex.z-dn.net/?f=W%28x%29%3D%20%5Cleft%7C%5Cbegin%7Barray%7D%7Bcc%7Dy_1%28x%29%26y_2%28x%29%5C%5Cy%27_1%28x%29%26y%27_2%28x%29%5Cend%7Barray%7D%5Cright%7C)
![= \left|\begin{array}{cc}x^4&x^6\\4x^3&6x^5\end{array}\right|](https://tex.z-dn.net/?f=%3D%20%5Cleft%7C%5Cbegin%7Barray%7D%7Bcc%7Dx%5E4%26x%5E6%5C%5C4x%5E3%266x%5E5%5Cend%7Barray%7D%5Cright%7C)
=x⁴×6x⁵- x⁶×4x³
=6x⁹-4x⁹
=2x⁹
≠0
The functions satisfy the differential equation and linearly independent since W(x)≠0
Therefore the general solution is
![y= c_1x^4+c_2x^6](https://tex.z-dn.net/?f=y%3D%20c_1x%5E4%2Bc_2x%5E6)
Answer: 15/24...i'm not sure though *scratches head*